Relationship Characteristics Soil, Fertilization and Outcome of Rice in Village Lubuk Pinang, Mukomuko - Weri Akmaldi; M. Faiz Barchia; Dwi Wahyuni Ganefianti (TERRA : Journal of Land Restoration, 2020)
This study aims to determine the close relationship between the characteristics of paddy soils and rice yields in Lubuk Pinang, the Manjunto Air Irrigation area, and to determine the level of applied technology of farmers and rice yields in Lubuk Pinang, the Air Manjunto Irrigation area. This research was conducted in April 2018 until June 2018 in Lubuk Pinang, Lubuk Pinang District, Mukomuko Regency. The study was conducted by survey method. Data as collected through direct observation in the field and soil analysis at the Soil Science Laboratory of Bengkulu University. The results showed that the coefficient regression soil pH (X1 ) is 0.208 to 0.875 sig t values are not real in the statistics. The regression coefficient cation exchange capacity (X2 ) is -0.018 with t sig value 0,781. Regression coefficient peat depth (X3 ) is -0.002 to 0.814 sig t values are not real in the statistics. Regression coefficient levels of soil organic C (X4 ) is -0.507 to 0.307 sig t values are not real in the statistics.